CdS supported on electrochemically reduced rGO for photo reduction of water to hydrogen - Ranjan R.; Kumar M.; Sinha A.S.K. (My University, 2025)
The paper reports synthesis of CdS supported rGO where reduction of GO to rGO was carried out electrochemically in situ. This catalyst had a better activity for photo-electrochemical dissociation of water to hydrogen. Catalysts were characterized by XRD, FTIR, DRS, XPS, EIS and Mott-Schottky analysis. It is reported that this catalyst showed formation of heterojunction at the interface of CdS and rGO by chemical interaction between the two. This resulted in a greater band bending, a higher charge carrier density, low resistance for electronic mobility and low recombination rate. A better activity of the catalyst is due to the above mentioned attributes. © 2019 Hydrogen Energy Publications LLC